Left Ventricular Noncompaction Is Associated with Valvular Regurgitation and a Variety of Arrhythmias - Qing Li; Lianjie Miao; Lihong Xia; Hala Y. Abdelnasser; Fang Zhang; Yangyang Lu; Anika Nusrat; Mantasha Tabassum; Juxiang Li; Mingfu Wu (Journal of Cardiovascular Development and Disease, 2022)
Left ventricular noncompaction (LVNC) is a type of cardiomyopathy characterized anatomically by prominent ventricular trabeculation and deep intertrabecular recesses. The mortality associated with LVNC ranges from 5% to 47%. The etiology of LVNC is yet to be fully understood, although decades have passed since its recognition as a clinical entity globally. Furthermore, critical questions, i.e., whether LVNC represents an acquired pathology or has a congenital origin and whether the reduced contractile function in LVNC patients is a cause or consequence of noncompaction, remain to be addressed. In this study, to answer some of these questions, we analyzed the clinical features of LVNC patients. Out of 9582 subjects screened for abnormal cardiac functions, 45 exhibit the characteristics of LVNC, and 1 presents right ventricular noncompaction (RVNC). We found that 40 patients show valvular regurgitation, 39 manifest reduced systolic contractions, and 46 out of the 46 present different forms of arrhythmias that are not restricted to be caused by the noncompact myocardium. This retrospective examination of LVNC patients reveals some novel findings: LVNC is associated with regurgitation in most patients and arrhythmias in all patients. The thickness ratio of the trabecular layer to compact layer negatively correlates with fractional shortening, and reduced contractility might result from LVNC. This study adds evidence to support a congenital origin of LVNC that might benefit the diagnosis and subsequent characterization of LVNC patients.